2021
DOI: 10.18502/jmehm.v14i14.7669
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying the concept of conscience in nurses’ ethical performance in Iran: a concept analysis study

Abstract: Although conscience, as an ethical concept, has emerged widely in the field of nursing, its functional meaning and its effects on nurses' performance are not clear. Therefore, the present study aimed to analyze the concept of conscience in the context of Iranian nurses’ ethical performance.    This study used a hybrid model including theoretical, fieldwork, and final analytic stages. In the theoretical phase, English and Persian articles published up to 2020 and indexed by scientific databases were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…This motivates employees to take responsibility for their own duties and increase their engagement in achieving their career goals [70]. Nurses' conscientiousness guides them in making ethical decisions based on ethical professional codes and guidelines [71,72]; ethics-based leadership skills play a major role in this regard [47,70,[73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…This motivates employees to take responsibility for their own duties and increase their engagement in achieving their career goals [70]. Nurses' conscientiousness guides them in making ethical decisions based on ethical professional codes and guidelines [71,72]; ethics-based leadership skills play a major role in this regard [47,70,[73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been no previous study in Turkey of nurses' perception of conscience, similar results have been reported in literature from studies conducted in other countries. 10,11 In terms of gender roles, as it is still mothers who take care of children, the pandemic was more difficult for working mothers. 6,18 This shows that gender significantly affects the perception of conscience and sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, problems of conscience may negatively affect the service and health of the patient. 11 Conscience is one of the concepts of nursing ethics, which is fundamental for nursing, improves ethical nursing care and positively affects nursing practices. 12 It has been shown that nurses who listen to their conscience have fewer conflicts on issues of conscience and can provide high-quality care in practice.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to what is stated in the texts, in nursing, conscience is defined as authority, a warning signal, a feeling and sensitivity, a valuable asset, a burden and a responsibility, an essence of nursing and a culture-dependent phenomenon ( 4 , 8 , 9 ). In nursing practice, conscience has been broadly considered as a basis for ethical affairs and ethical nursing care ( 10 ). The role of conscience in nursing is expressed in different ways, such as warning, a guide, a sensitivity elevator and a moral guide to the patient's needs ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of conscience in nursing is expressed in different ways, such as warning, a guide, a sensitivity elevator and a moral guide to the patient's needs ( 11 , 12 ). Jodaki et al also consider conscience as an existential command center that is associated with a tormented conscience and a sense of guilt if neglected, but one that brings a feeling of peace and satisfaction when applied in the care process ( 10 ).…”
Section: Introductionmentioning
confidence: 99%